Aplikasi Absensi Non ASN Berbasis Web - Wilianto Wilianto; Asep Muhidin; Abdul Halim Anshor (Jurnal Media Infotama, 2023)
Presence is crucial in a government institution. With an effective attendance system, it is hoped that it can assist in controlling the task completion process. The Attendance Recording System used in the Public Section applies fingerprint technology. Fingerprint is one of the information technology innovations that makes it easier to record employee activities every day. At this time employees do not take attendance using a fingerprint machine and return to using a manual system. The system is done manually, namely by signing the attendance book that has been provided by the staffing department. The purpose of developing this application is to facilitate, and speed up, employees in taking attendance and managing attendance outside the office. The method used in developing web-based non-ASN attendance applications is the waterfall model. as a structured software approach, starting from the stages of analysis, design, coding, testing, to the support stage. The PHP programming language, Laravel Framework and Database Management System (DBMS) use MySQL. The result of this research is the development of a web-based non-asn attendance application for non-asn employees in the general section of the regional secretariat of Bekasi district